The Relationship Between Diet and Healthy, Clean-Living Behavior with The Nutritional Status of Scavengers - Haryati, Angelina; Mutiara, Erli; Emilia, Elisi; Purba, Rasita; Rukmana, Erni (Nutrition Study Program, Faculty of Medicine, Universitas Negeri Semarang, Indonesia, 2024)
Introduction: This study aims to determine the relationship between dietary patterns and healthy, clean-living behavior with scavenger’s nutritional status in Batam City. Methods: This study used a cross-sectional design. The location was conducted at Garbage’s Final Disposal Site (TPA) Telaga Punggur in Batam City in December-February 2023. A sample size of 79 Scavengers was obtained using simple random sampling—data collection using anthropometric measurements and questionnaires. Bivariate analysis was performed with the Spearman rank test, and multivariate analysis was performed with multiple linear regression tests. Results: The study's results showed poor dietary patterns (83,5%). Clean and healthy living behavior was in the poor category (82,3%)—the nutritional status of Scavengers was in the skinny nutritional status category (32,9%). The Spearman rank test shows a significant relationship between dietary patterns and nutritional status and a significant relationship between healthy, clean-living behavior and nutritional status (p=0,002, 0,021). Conclusion: Multiple linear regression test shows there is a significant relationship between the dietary pattern and healthy, clean-living behavior with nutritional status of Scavengers Y = 14,358 + 0,137X1 + 0,074X2 (p=0,003), that meaning there is a relationship between the dietary pattern and healthy clean-living behavior with the nutritional status of Scavengers in Batam City.